Mengenal Bank “Syariah” Lembaga Keuangan untuk Umum - Fauzi Solihin (The Winners, 2001)
The article objective is to compare Syariah banking system to common banking system. It is concluded that Syariah banking system can be alternative banking system to any body who expect profit sharing as the replacement of common interest mechanism.